Penicillin resistance and serotypes/serogroups of Streptococcus pneumoniae in nasopharyngeal carrier children younger than 2 years in Lima, Peru - Ochoa T.J. (2005)
The purpose of this study was to determine the carriage rate, susceptibility pattern, and serotype distribution of Streptococcus pneumoniae in the nasopharynx of children younger than 2 years old in Lima, Peru. A total of 666 children were evaluated during 3 periods, 1997, 2001, and 2003. The overall pneumococcal carrier rate was 41%. Reduced susceptibility to penicillin was found in 5% (4/75) of isolates in 1997, 20% (15/75) in 2001, and 37% (40/109) in 2003. Reduced susceptibility to ceftriaxone was found in 12% of isolates in 2003. Serogroups 6, 19, 23, 15, and 14 accounted for 68% of all the isolates and for 81% of the penicillin-nonsusceptible strains. Only 65% of the isolated strains had serogroups found in the 7-valent conjugate pneumococcal vaccine. This highlights the importance of regional surveillance studies for effective vaccine strategies and treatment protocols.